Complete mitochondrial genome of Acheilognathus hypselonotus Bleekers (Cypriniformes: Cyprinidae) in China's Dianshan Lake. Issue 12 (2nd December 2021) - Zhu, Lin; Che, Xuan; Liu, Xingguo; Wang, Xiaodong; Wang, Jie; Cheng, Guofeng; Chen, Xiaolong; Chen, Xin
Abstract: The complete mitochondrial genome sequence of Acheilognathus hypselonotus is firstly described in this article. The total length of the mitogenome is 16, 706 bp. It contains 13 protein-coding genes, 22 tRNA genes and 2 ribosomal RNA genes. The overall base composition of the H-strand is 29.03% A, 25.6% C, 28.13% T, and 17.25% G, with an A＋T bias of 57.16%. The phylogenetic analysis result showed that the A. hypselonotus, A. typus and A. macropterus were a close relationship.